MINING ARCHAEOLOGY IN MINAS GERAIS - BRAZIL: HISTORY, TECHNIQUES AND VESTIGES AS PALIMPSESTS OF MEMORY: historia, técnicas y huellas como palimpsestos de la memoria - Martins Campos Akinruli, Luana Carla (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2024)
The mercantilist orientation was determinant for the mining direction as one of the main economic activities of colonial reality which had slave labor as its fundamental source of labor. From this mining activity, social relations were defined among several historical agents, who were directly involved in the social configuration of the prospective Nation-States in the Americas as well as in the development of industrial capitalism in Europe. This manuscript aims to promote the debate on the colonial mining context in Minas Gerais, the main mining hotspot in Brazil. Thus, we address the history and archaeology of mining in a perspective of memory palimpsests, a very complex and deep history, marked by a long duration of conflicts circumscribed by the mining interests of large mining companies that have always explored these lands.  To this effect, reflections will be undertaken regarding the history of mining, its techniques and technologies, the tensions between involved agents and agencies; the environmental impacts; the interlocutions between objects and (i)materialities.